2003
DOI: 10.1037/0022-3514.84.1.221
|View full text |Cite
|
Sign up to set email alerts
|

Negative affectivity and drug use in adolescent boys: Moderating and mediating mechanisms.

Abstract: This investigation examined variables that might qualify or detail the widely accepted relation between negative affectivity and drug use in adolescent boys. In Study 1, 311 boys (15-17 years old) completed inventories of negative affectivity, positive affectivity, constraint, delinquency, peer delinquency, and drug use. Negative affectivity was positively related to drug use, but only for individuals exhibiting high peer delinquency or low constraint. Study 2 examined mechanisms for this relation by following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 101 publications
2
21
1
Order By: Relevance
“…As was described earlier with regard to conscientiousness and agreeableness, constraint has also been related to criminal behavior over time (Krueger, 2002). Low constraint (in interaction with negative affectivity) has also been related to drug use (Shoal & Giancola, 2003).…”
mentioning
confidence: 61%
“…As was described earlier with regard to conscientiousness and agreeableness, constraint has also been related to criminal behavior over time (Krueger, 2002). Low constraint (in interaction with negative affectivity) has also been related to drug use (Shoal & Giancola, 2003).…”
mentioning
confidence: 61%
“…Multiple studies have identified a relationship between negative affect and increased substance use during adolescence (Colder and Chassin, 1997;Myers et al, 2003;Shoal and Giancola, 2003;Stice et al, 1998), suggesting that individuals use substances to alleviate or cope with negative affect (Sher and Trull, 1994). Several researchers, however, have found this relationship to be negative or inconclusive (Brook et al, 1986;McGue et al, 2001;Stice et al, 1998;White et al, 1986).…”
Section: Negative Affectmentioning
confidence: 99%
“…They found these behaviors to covary significantly, indicating that adolescents high in negative affectivity are prone to engage in clusters of dangerous and antisocial activities as detailed in Jessor and Jessor's (1977) problem behavior theory. Evidence from other longitudinal studies indicates that the experience of negative affect is mediated in its relation to later drug use by general delinquency (Shoal & Giancola, 2003). Likewise, "difficult temperament," which includes irritability, intense reactions to stimuli, and general negative mood (Thomas & Chess, 1977) appears to be mediated in its relation to later drug use by general antisocial behavior (Giancola & Parker, 2001).…”
Section: Empirical Evidence: Personal Delinquency and Attitudes Towarmentioning
confidence: 99%
“…For example, Giancola and Parker (2001) found that peer delinquency mediates the relation between difficult temperament (which includes negative mood and intense reactions to stimuli) and drug use later in adolescence. Additionally, Shoal and Giancola (2003) showed that affiliation with delinquent peers mediates the relation between negative affectivity and overall substance use two years later. A significant limitation of this research, however, is that it has not pitted different delinquency variables against one another in order to determine which aspects of delinquency are most strongly related to affect and drinking.…”
Section: Empirical Evidence: Affiliation With Delinquent Peers As a Mmentioning
confidence: 99%
See 1 more Smart Citation